Supramolecular nanoparticles that target phosphoinositide-3-kinase overcome insulin resistance and exert pronounced antitumor efficacy - Kulkarni, Ashish A.; Roy, Bhaskar; Rao, Poornima S.; Wyant, Gregory A.; Mahmoud, Ayaat; Ramachandran, Madhumitha; Sengupta, Poulomi; Goldman, Aaron; Kotamraju, Venkata Ramana; Basu, Sudipta; Mashelkar, Raghunath Anant; Ruoslahti, Erkki; et al. (Cancer Research, 2013)
The centrality of phosphoinositide-3-kinase (PI3K) in cancer etiology is well established, but clinical translation of PI3K inhibitors has been limited by feedback signaling, suboptimal intratumoral concentration, and an insulin resistance ``class effect.'' This study was designed to explore the use of supramolecular nanochemistry for targeting PI3K to enhance antitumor efficacy and potentially overcome these limitations. PI3K inhibitor structures were rationally modified using a cholesterol-based derivative, facilitating supramolecular nanoassembly with L-alpha-phosphatidylcholine and DSPE-PEG [1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polythylen e glycol)]. The supramolecular nanoparticles (SNP) that were assembled were physicochemically characterized and functionally evaluated in vitro. Antitumor efficacy was quantified in vivo using 4T1 breast cancer and K-Ras(LSL/+)/Pten(fl/fl) ovarian cancer models, with effects on glucose homeostasis evaluated using an insulin sensitivity test. The use of PI103 and PI828 as surrogate molecules to engineer the SNPs highlighted the need to keep design principles in perspective; specifically, potency of the active molecule and the linker chemistry were critical principles for efficacy, similar to antibody-drug conjugates. We found that the SNPs exerted a temporally sustained inhibition of phosphorylation of Akt, mTOR, S6K, and 4EBP in vivo. These effects were associated with increased antitumor efficacy and survival as compared with PI103 and PI828. Efficacy was further increased by decorating the nanoparticle surface with tumor-homing peptides. Notably, the use of SNPs abrogated the insulin resistance that has been associated widely with other PI3K inhibitors. This study provides a preclinical foundation for the use of supramolecular nanochemistry to overcome current challenges associated with PI3K inhibitors, offering a paradigm for extension to other molecularly targeted therapeutics being explored for cancer treatment. (C)2013 AACR.

Reporter nanoparticle that monitors its anticancer efficacy in real time - Kulkarni, Ashish; Rao, Poornima; Natarajan, Siva; Goldman, Aaron; Sabbisetti, Venkata S.; Khater, Yashika; Korimerla, Navya; Chandrasekar, Vineethkrishna; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The ability to monitor the efficacy of an anticancer treatment in real time can have a critical effect on the outcome. Currently, clinical readouts of efficacy rely on indirect or anatomic measurements, which occur over prolonged time scales postchemotherapy or postimmunotherapy and may not be concordant with the actual effect. Here we describe the biology-inspired engineering of a simple 2-in-1 reporter nanoparticle that not only delivers a cytotoxic or an immunotherapy payload to the tumor but also reports back on the efficacy in real time. The reporter nanoparticles are engineered from a novel two-staged stimuli-responsive polymeric material with an optimal ratio of an enzyme-cleavable drug or immunotherapy (effector elements) and a drug function-activatable reporter element. The spatiotemporally constrained delivery of the effector and the reporter elements in a single nanoparticle produces maximum signal enhancement due to the availability of the reporter element in the same cell as the drug, thereby effectively capturing the temporal apoptosis process. Using chemotherapy-sensitive and chemotherapy-resistant tumors in vivo, we show that the reporter nanoparticles can provide a real-time noninvasive readout of tumor response to chemotherapy. The reporter nanoparticle can also monitor the efficacy of immune checkpoint inhibition in melanoma. The self-reporting capability, for the first time to our knowledge, captures an anticancer nanoparticle in action in vivo.
Keywords: chemotherapy; immunotherapy; monitoring; nanoparticle; reporter